2020
DOI: 10.1111/raq.12483
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of cold water aquaculture: a review of likely scenarios as climate changes in the Gulf of Maine

Abstract: Climate change is one of the biggest challenges facing development and continuation of sustainable aquaculture in temperate regions. We primarily consider the ecological and physical resilience of aquaculture in the Gulf of Maine (GoM), where a thriving industry includes marine algae, extensive and intensive shellfish aquaculture, and a well-established Atlantic salmon industry, as well as the infrastructure required to support these economically important ventures. The historical record of sea surface tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 296 publications
(514 reference statements)
0
21
0
Order By: Relevance
“…First, priming the gametophyte generation of the kelp Alaria esculenta for 3 days at 22 • C (compared with 12 • C) enhanced their survival under increased temperatures, and the growth of the derived sporophyte generation (Quigley et al, 2018). Second, cultivation of Saccharina japonica gametophytes at 22-24 • C increased the heat-tolerance of the derived sporophytes by 2 • C (Wu and Pang, 1998) in Bricknell et al (2021). Third, in the fucoid brown alga Fucus vesiculosus, storage of parental tissue at a higher temperature (14 • C versus 4 • C), or acclimation of embryos to 29 • C significantly increased their survival by 30-50% under 33 • C (Li and Brawley, 2004).…”
mentioning
confidence: 99%
“…First, priming the gametophyte generation of the kelp Alaria esculenta for 3 days at 22 • C (compared with 12 • C) enhanced their survival under increased temperatures, and the growth of the derived sporophyte generation (Quigley et al, 2018). Second, cultivation of Saccharina japonica gametophytes at 22-24 • C increased the heat-tolerance of the derived sporophytes by 2 • C (Wu and Pang, 1998) in Bricknell et al (2021). Third, in the fucoid brown alga Fucus vesiculosus, storage of parental tissue at a higher temperature (14 • C versus 4 • C), or acclimation of embryos to 29 • C significantly increased their survival by 30-50% under 33 • C (Li and Brawley, 2004).…”
mentioning
confidence: 99%
“…Overall warming trends have been more pronounced in the Northern than the Southern Hemisphere [ 24 ] and warming rates are generally greater at higher latitudes when compared to equatorial regions. In particular, MHW, defined as temperature anomalies where sea surface temperatures exceed the 90th percentile of the local long-term climatology for at least 5 consecutive days [ 25 ], can be particularly damaging for marine species [ 26 ], with potential impacts on aquaculture production (e.g., [ 27 ]). A study by Oliver et al [ 12 ] reported that MHW intensity and annual MHW days are increasing worldwide, with significant, widespread and persistent effects on marine ecosystems.…”
Section: Adult Atlantic Salmon Thermal Tolerance and Physiological Responses To Heat Stressmentioning
confidence: 99%
“…For example, the annual cumulative intensity of MHW has increased 340% over the past 30 years in southern Norway (Flødevigen Research Station) [ 30 ], with unusually high water temperatures (>18 °C) being registered in the south of Norway in recent years [ 31 ]. In the Gulf of Maine, where the salmon aquaculture industry is also well established, surface waters have increased at a rate of +0.23 °C per year in the past decade [ 27 ]. Moreover, records of a persistent MHW over the Gulf of Maine in 2012 led to a peak of >18 °C in sea surface temperature [ 27 ].…”
Section: Adult Atlantic Salmon Thermal Tolerance and Physiological Responses To Heat Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…They have also been an important source of human food. Due to climate change and other anthropogenic factors, global kelp populations have faced a drastic decline (Moy and Christie 2012, Wernberg et al 2019, Bricknell et al 2020. Now kelp farming is largely replacing wild harvests: over 30 million metric tons of seaweed were harvested in 2018, of which 97% came from farms (FAO, 2020).…”
Section: Introductionmentioning
confidence: 99%